Preparation, Characterization and Utilization of Amidoximated Poly(AN/MAA)-grafted Alhagi Residues for the Removal of Zn(II) Ions from Aqueous Solution - A.A. Khalil; H.H. Sokker; A. Al-Anwar; A. Abd El-Zaher; A. Hashem (Adsorption Science & Technology)
Radiation grafting by the mutual method of methacrylic acid/acrylonitrile (MAA/AN) onto Alhagi residues in the presence of dimethylformamide (DMF) as a solvent is discussed. The factors affecting the radiation graft copolymerization were investigated. These included radiation dose, co-monomer composition and concentration. The grafted samples were characterized using FT-IR spectroscopy and scanning electron microscopy (SEM), as well as by the estimation of their nitrogen and carboxyl group contents. The grafted samples were then amidoximated by treatment with hydroxylamine hydrochloride in an alkaline medium. Such amidoximated poly(MAA/AN)-grafted Alhagi residues were utilized for the removal of Zn(II) ions from aqueous solution by adsorption and the factors affecting such adsorption processes were studied. These factors were the pH of the adsorbate solution, the adsorbent dosage, the contact time and the adsorption temperature. The adsorption data obeyed the Langmuir and Freundlich isotherms. The Langmuir adsorption capacity (Q max ) of the amidoximated poly(MAA/AN)-grafted Alhagi residues towards Zn(II) ions was found to be 212.76 and 344.8 mg/g at 30 °C and 50 °C, respectively. Similarly, the Freundlich constants, K F and 1/n, at 30 °C were found to be 21.47 and 0.3489, respectively. The study showed that amidoximated poly(MAA/AN)-grafted Alhagi residues were effective in the adsorption of Zn(II) ions from aqueous solutions. The thermodynamics parameters of the adsorption process, viz. ΔH 0 , ΔG 0 and ΔS 0 , were evaluated. The results showed that the adsorption of Zn(II) ions onto amidoximated poly(MAA/AN)-grafted Alhagi residues was endothermic and spontaneous. The adsorption data followed second-order kinetics.